2021
DOI: 10.1026/0942-5403/a000334
|View full text |Cite
|
Sign up to set email alerts
|

Callous-unemotional Traits, moralische Identität und Bullying im Jugendalter

Abstract: Zusammenfassung. Theoretischer Hintergrund: Die Rolle der Moral im Kontext pro- und antisozialer Verhaltensweisen wird sowohl national als auch international diskutiert. Im Zusammenhang mit antisozialen Verhaltensweisen von Jugendlichen werden zudem vermehrt Callous-unemotional Traits betrachtet. Fragestellung: Die vorliegende Studie untersucht den Zusammenhang zwischen CU-Traits, der moralischen Identität und Bullying. Methode: Insgesamt bearbeiteten N = 749 Jugendliche einen Fragebogenkatalog. SPSS und AMOS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 57 publications
(69 reference statements)
1
3
0
Order By: Relevance
“…The higher the CU- traits the lower the expressions of moral identity. These findings speak to the influence of personality traits on identity and are in line with the findings of Schipper and Koglin ( 2021a ). In order to prevent serious development problems the relevance for preventive interventions is emphasized by Frick and White ( 2008 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The higher the CU- traits the lower the expressions of moral identity. These findings speak to the influence of personality traits on identity and are in line with the findings of Schipper and Koglin ( 2021a ). In order to prevent serious development problems the relevance for preventive interventions is emphasized by Frick and White ( 2008 ).…”
Section: Discussionsupporting
confidence: 91%
“…CU-traits have been increasingly analyzed in the context of moral disengagement, but not in the context of moral identity. Recent studies show that high moral identity in adolescents is associated with lower levels of CU-traits (Schipper & Koglin, 2021a ). This direction of correlations is consistent with the assumption that CU-traits are characterized by e.g.…”
Section: Current Studymentioning
confidence: 99%
“…In addition to the mentioned developmental outcomes in middle childhood, such as conduct disorder or internalizing problems (Gao & Zhang, 2016;Willoughby et al, 2015), callous-unemotional traits are also associated with impairments in moral development (Craig et al, 2021). Most analysis of associations between callous-unemotional traits and moral development were conducted in adolescence (Kokkinos et al, 2016;Schipper & Koglin, 2021;Vasconcelos et al, 2021) rather than in middle childhood (Thornberg & Jungert, 2017). Frick et al (2014) suggested that callous-unemotional traits could be seen as a misdevelopment of conscience.…”
Section: Morality In Middle Childhood and Associations With Callous-u...mentioning
confidence: 99%
“…Callousness does not seem to be signi cantly associated with the moral self for the present sample. Children who value the concerns and feelings of others regard being a moral person as crucial(Schipper & Koglin, 2021). Accordingly, the moral self can be highlighted as a possible construct that is impaired in development to the detriment of children and, in turn, is associated with behavioral problems(Gini et al, 2021;Wang et al, 2020).…”
mentioning
confidence: 99%